Optimized NMR Experiments for the Isolation of I=1/2 Manifold Transitions in Methyl Groups of Proteins. Issue 1 (5th December 2019) - Tugarinov, Vitali; Karamanos, Theodoros K.; Ceccon, Alberto; Clore, G. Marius
Abstract: Optimized NMR experiments are developed for isolating magnetization belonging to the I =1/2 manifolds of 13 CH3 methyl groups in proteins, enabling the manipulation of the magnetization of a 13 CH3 moiety as if it were an AX ( 1 H‐ 13 C) spin‐system. These experiments result in the same 'simplification' of a 13 CH3 spin‐system that would be obtained from the production of { 13 CHD2 }‐methyl‐labeled protein samples. The sensitivity of I =1/2 manifold‐selection experiments is a factor of approximately 2 less than that of the corresponding experiments acquired on { 13 CHD2 }‐labeled methyl groups. The methodology described here is primarily intended for small‐to‐medium sized proteins, where the losses in sensitivity associated with the isolation of I =1/2 manifold transitions can be tolerated. Several NMR applications that benefit from simplification of the 13 CH3 (AX3 ) spin‐systems are described, with an emphasis on the measurements of methyl 1 H‐ 13 C residual dipolar couplings in a { 13 CH3 }‐methyl‐labeled deletion mutant of the human chaperone DNAJB6b, where modulation of NMR signal intensities due to evolution of methyl 1 H‐ 13 C scalar and dipolar couplings follows a simple cosine function characteristic of an AX ( 1 H‐ 13 C) spin‐system, significantly simplifying data analysis. Abstract : Optimized NMR pulse schemes are developed for a more efficient and complete isolation of magnetization belonging to I =1/2 manifolds in methyl groups of proteins.